2022
DOI: 10.3390/molecules27031129
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Luminescence Properties of 8-Coordinate Holmium(III) Complexes Containing 4,4,4-Trifluoro-1-Phenyl- and 1-(Naphthalen-2-yl)-1,3-Butanedionates

Abstract: A new series of mononuclear Ho3+ complexes derived from the β-diketonate anions: 4,4,4-trifluoro-1-phenyl-1,3-butanedioneate (btfa−) and 4,4,4-trifuoro-1-(naphthalen-2-yl)-1,3-butanedionate (ntfa−) have been synthesized, [Ho(btfa)3(H2O)2] (1a), [Ho(ntfa)3(MeOH)2] (1b), (1), [Ho(btfa)3(phen)] (2), [Ho(btfa)3(bipy)] (3), [Ho(btfa)3(di-tbubipy)] (4), [Ho(ntfa)3(Me2bipy)] (5), and [Ho(ntfa)3(bipy)] (6), where phen is 1,10-phenantroline, bipy is 2,2′-bipyridyl, di-tbubipy is 4,4′-di-tert-butyl-2,2′-bipyridyl, and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 86 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…Room temperature fluorescence measurements of the synthesized metal-organic framework were carried out from the sample in the solid state form using Cary Eclipse spectrophotometer. Ho(III) complexes are generally found to show Visible and NIR luminescence [41,42], but the holmium bi-tartrate trihydrate MOF emits in visible region. There are two most luminescent energy states 5 F 5 and 5 S 2 in Ho(III) ion and is reported that the state, 5 F 5 is responsible for NIR luminescence [43].…”
Section: Photoluminescence Studiesmentioning
confidence: 99%
“…Room temperature fluorescence measurements of the synthesized metal-organic framework were carried out from the sample in the solid state form using Cary Eclipse spectrophotometer. Ho(III) complexes are generally found to show Visible and NIR luminescence [41,42], but the holmium bi-tartrate trihydrate MOF emits in visible region. There are two most luminescent energy states 5 F 5 and 5 S 2 in Ho(III) ion and is reported that the state, 5 F 5 is responsible for NIR luminescence [43].…”
Section: Photoluminescence Studiesmentioning
confidence: 99%